Students’ Perceptions of Digital Literacy-Based Media in English Language Learning - Nurlita, Reekhan; Taufiq, Wahyu (Universitas Siliwangi, 2025)
This study explores students’ perceptions of the use of digital literacy-based media in English language learning. The research was conducted at a Senior High School in Sidoarjo, involving eleventh-grade students as participants. Using a qualitative descriptive method, data were collected through interviews, classroom observations, and document analysis. The results indicate that students generally responded positively to the integration of digital tools such as YouTube, Canva, Duolingo, Elsa Speak, Kahoot, and Quizizz. These tools were seen as more interactive, flexible, and motivating compared to traditional learning methods. Students reported increased engagement, creativity, and confidence in learning English. However, several challenges were also noted, including unstable internet connections and distractions from unrelated digital content. The study concludes that digital literacy-based media significantly enhance the quality and effectiveness of English learning when supported by proper guidance and instructional planning.